Discovery of Benzo[f]indole-4,9-dione Derivatives as New Types of Anti-Inflammatory Agents - You-Ren Chen (International Journal of Molecular Sciences, 2015)
Certain benzo[f]indole-4,9-dione derivatives were synthesized and evaluated for their inhibitory effects on superoxide anion generation and neutrophil elastase (NE) release in formyl-l-methionyl-l-leucyl-l-phenylalanine (fMLF)-activated human neutrophils. Results indicated that (Z)-1-benzyl-4-(hydroxyimino)-1H-benzo[f]indol-9(4H)-one (10) showed a potent dual inhibitory effect on NE release and superoxide anion generation with IC50 value of 2.78 and 2.74 μM respectively. The action mechanisms of 10 in human neutrophils were further investigated. Our results showed that compound 10 did not alter fMLF-induced phosphorylation of Src (Src family Y416). Notably, phosphorylation of Akt (S473) and mobilization of [Ca2+]i caused by fMLF was inhibited by compound 10. Further structural optimization of 10 is ongoing.